2007
DOI: 10.1086/510782
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the KIAA0196 Gene at the SPG8 Locus Cause Hereditary Spastic Paraplegia

Abstract: Hereditary spastic paraplegia (HSP) is a progressive upper-motor neurodegenerative disease. The eighth HSP locus, SPG8, is on chromosome 8p24.13. The three families previously linked to the SPG8 locus present with relatively severe, pure spastic paraplegia. We have identified three mutations in the KIAA0196 gene in six families that map to the SPG8 locus. One mutation, V626F, segregated in three large North American families with European ancestry and in one British family. An L619F mutation was found in a Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
151
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(162 citation statements)
references
References 33 publications
10
151
0
1
Order By: Relevance
“…S8C). Finally, given the association of Strumpellin with HSP (15), and the fact that the known mutations do not affect SHRC assembly, it will be important to examine the effect of these mutations on the cellular and biochemical activities of the SHRC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S8C). Finally, given the association of Strumpellin with HSP (15), and the fact that the known mutations do not affect SHRC assembly, it will be important to examine the effect of these mutations on the cellular and biochemical activities of the SHRC.…”
Section: Resultsmentioning
confidence: 99%
“…Strumpellin has no identifiable subdomains, but the protein is predicted to be highly helical. The gene encoding Strumpellin was recently found mutated in the neurodegenerative disease hereditary spastic paraplegia (HSP), but there is no understanding of Strumpellin function or how its mutations give rise to disease (14,15). Finally, no functions have been reported for SWIP, which like Strumpellin has no recognizable subdomains and is predicted to be highly helical.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, genetic deletion of WASH in mice results in early embryonic lethality Xia et al, 2013). Interestingly, mutations in the genes encoding KIAA1033 and strumpellin have been linked to intellectual disability (ID) syndromes (Elliott et al, 2013;Ropers et al, 2011), and separate mutations in strumpellin have been found in patients with hereditary spastic paraplegia (HSP) (Valdmanis et al, 2007). However, the mechanism by which WASH deregulation contributes to the pathology of either disease is unclear.…”
Section: Jmymentioning
confidence: 99%
“…Mutations in the SPG 6 15 and SPG 8 16 are pure HSPs that have already been identified in the Brazilian population. SPG 6 presents as a slowly progressive, mostly pure spastic paraplegia in early-adulthood 15 (Table 1).…”
Section: Classificationmentioning
confidence: 74%